A Pre-Test for a Technology Acceptance Implementation to Enhance Student Learning on Campus - Saleh, Nor Shela; Abdul Malek Akalil Malek Razak,; Ramanathan Ashwin Thanneermalai,; Muhamad Faiq Mustafa,; Nurul Amin Salim,; Munira Zahrah Mohamad Zaihan,; Fatin Nabilah Mohd Talib,; Ummu Khadijah Abdul Malik, (Human Sustainability Procedia, 2025)
Technology plays a pivotal role in transforming national educational initiatives. Within this context, technology empowerment is identified to highlight the use of ICT to enhance the quality of learning in Malaysia. Although technology integration in education is increasing, some students have yet to experience its advantages fully. To investigate this issue, a study was conducted at Universiti Tun Hussein Onn Malaysia with three primary objectives: to assess students' acceptance of technology, to identify the factors influencing this acceptance, and to analyze the relationship between technology acceptance and academic performance. The research employed a quantitative approach, distributing questionnaires to students across various faculties. The data collected were analyzed using descriptive and inferential statistics. The findings indicated a moderate to high level of technology acceptance among students, with technology skills, infrastructure support, and student attitudes identified as the major contributing factors. Additionally, a positive impact was observed between technology acceptance and academic performance, particularly regarding access to learning resources. In conclusion, fostering technology acceptance can significantly improve learning effectiveness, provided that suitable technological resources and continuous skills development are available. This advancement indirectly contributes to attaining Sustainable Development Goal 4, which focuses on ensuring Quality Education (SDG 4).